Actualización en sobrecrecimiento bacteriano intestinal y dificultades en su diagnóstico - Muñoz D., Pablo; Collado H., Raúl; Landskron R., Glauben; Gonzalez A., Javiera; Massardo V., Teresa (Revista Hospital Clínico Universidad de Chile, 2012)
This is a short review related with the current concepts and controversies in the diagnosis of intestinal bacterial overgrowth. This is a relatively complex entity present in diverse pathologies. Its adequate diagnosis has impact in the therapy and management of the patients with this condition.